Post-thymectomy myasthenia gravis: a case report and systematic review of literature. Issue 12 (2nd December 2021) - Gurowich, Louise; Yiin, Gabriel; Maxwell, Adam; Rice, Alexandra
Abstract : Myasthenia gravis (MG) is an autoimmune condition affecting the neuromuscular junction characterised by weakness and fatiguability, carrying a high morbidity if treatment is delayed. A clear association with thymoma has led to management with thymectomy as a common practice, but MG presenting post-thymectomy has rarely been reported. We present a case of an 82- year-old woman developing fatigue, ptosis and dysarthria 3 months after thymectomy. After a clinical diagnosis of MG was made, she responded well to prompt treatment with prednisolone and pyridostigmine. Her anti-acetylcholine receptor antibody (anti-AChR) subsequently came back positive. Our systematic review reveals that post-thymectomy MG can be categorised as early-onset or late-onset form with differing aetiology, and demonstrated correlation between preoperative anti-AChR titres and post-thymectomy MG. The postulated mechanisms for post-thymectomy MG centre around long-lasting peripheral autoantibodies. Clinicians should actively look for MG symptoms in thymoma patients and measure anti-AChR preoperatively to aid prognostication.